2018
DOI: 10.1002/pmic.201800191
|View full text |Cite
|
Sign up to set email alerts
|

All Cats are Gray in the Dark: Enrichment/Depletion Approaches for Biomarker Discovery on Felis catus Plasma

Abstract: In veterinary medicine, assay performance is often affected by the lack of species-specific diagnostic tools. Reliable biomarkers might be identified by investigating biological fluids of the species of interest, but protein sequence databases are often incomplete and human-specific devices for reducing sample complexity might fail when applied to animal plasma. Here, seven commercial methods based on different capturing agents (anti-human antibodies, affinity ligands, mixture of antibodies and ligands, and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…The high efficacy can be explained by the high sequence homology (80.1%) of albumin, the most abundant HAP, between humans and dogs. 14,15 Previous research has also demonstrated successful immunodepletion of targeted HAPs from canine and bovine biological fluids using the human MARS-6 device. 19,22 Immunodepletion of feline plasma samples has been attempted previously, however researchers found that none of the four human-based HAP immunodepletion devices evaluated were efficacious.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The high efficacy can be explained by the high sequence homology (80.1%) of albumin, the most abundant HAP, between humans and dogs. 14,15 Previous research has also demonstrated successful immunodepletion of targeted HAPs from canine and bovine biological fluids using the human MARS-6 device. 19,22 Immunodepletion of feline plasma samples has been attempted previously, however researchers found that none of the four human-based HAP immunodepletion devices evaluated were efficacious.…”
Section: Discussionmentioning
confidence: 99%
“…19,22 Immunodepletion of feline plasma samples has been attempted previously, however researchers found that none of the four human-based HAP immunodepletion devices evaluated were efficacious. 15 These results were surprising, given that feline and human albumin also share a high degree of sequence homology (82.4%). 15 In contrast, our study demonstrated successful removal of albumin and likely IgG from feline plasma, which may reflect an increased antibody affinity for feline albumin in the MARS-2 kit compared to the previously tested devices.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations